PENERAPAN MODEL PROJECT BASED LEARNING DENGAN MEDIA KONKRET UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA KELAS V E DI SDN POLISI 1 KOTA BOGOR - Vindy Sunny; Fitri Siti Sundari; Mia Kurniasih (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
This study aims to determine the project-based learning model with concrete learning media on mathematics learning outcomes. This research was carried out at SDN Police 1 Bogor City in semester 2 of the 2022/2023 academic year. This research is collaborative classroom action research. This class action research uses the Kemmis and Mc Taggart models. Kemmis and Mc Taggart models. This study aims to: 1) describe the appropriate steps for using the PjBL model with concrete object media, 2) improve Mathematics learning outcomes through the PjBL model with concrete object media. This research data collection technique uses observation and tests. This research is a collaborative classroom action research and is carried out in three cycles, with each cycle consisting of planning, implementing actions, observation, and reflection. The results showed that the completeness of student learning outcomes has increased. In the first cycle, the completeness of student learning outcomes classically only reached 35.71%, not exceeding KKM by 85%. Then it increased in cycle II to 89.29% and has exceeded KKM. The results showed that the use of the PjBL model with concrete object media can improve the learning outcomes of Mathematics learning for grade V students of SDN Police 1 Bogor City for the 2022/2023 school year.